PENINGKATAN MOTIVASI DAN HASIL BELAJAR MATEMATIKA MENGGUNAKAN MODEL CONTEXTUAL TEACHING AND LEARNING DI KELAS XII TKJ SMK NEGERI 1 MUARA BUNGO - NICOLAS JUNIBINSAR SIMATUPANG (Jurnal Tunas Pendidikan, 2020)
The problem in this research is the low motivation and learning outcomes of students in Mathematics class XII Class XII TKJ SMK Negeri 1 Muara Bungo. The purpose of this study was to describe the increase in motivation in the CTL class XII model in motivation and learning outcomes. This research is a classroom action research with a quantitative approach. The research subjects were students of class XII TKJ SMK Negeri 1 Muara Bungo, totaling 22 people. The implementation of this study consisted of two cycles carried out by the researcher. Each cycle consists of planning, acting, observing and reflecting on each cycle. This research was conducted in the second semester of the 2019/2020 school year. The data of this research are videos, documentation, students' motivation questionnaire and test results. The results showed that there was an increase in learning motivation from cycle I to 65.22% and to cycle II to 80.68%. This indicates that the learning motivation of students increased according to the indicator, namely 80%, and the learning outcomes of students in the first cycle were 63.86%, while the second cycle increased to 81.81%. Seeing this research, using the CTL model in Mathematics learning needs to be applied and developed in order to improve the quality of education in the future.